Alas Purwo as the Heart of Culture and Tourist Attraction of Indonesia - Ainul Yaqin; Ginamutaafif; Imrotun Nabila; Ester Carolina Putri Nugraha (CV. Sekawan Siji, 2026)
This study aims to analyze the significance of Alas Purwo in Banyuwangi, East Java, Indonesia, as a cultural heartland for local communities and its unique potential as a tourist attraction for Indonesia. Employing a mixed-methods approach (qualitative and quantitative), this research explores the ritual practices, myths, beliefs, and traditional knowledge of communities surrounding Alas Purwo through in-depth interviews, participant observation, and document analysis. Surveys were also conducted to understand tourists' perceptions of Alas Purwo's natural and cultural attractions, as well as local communities' views on tourism development. The findings reveal that Alas Purwo is not only a conservation area with rich biodiversity but also a strong spiritual center and cultural identity for the people of Banyuwangi, reflected in various local traditions and narratives. The potential of Alas Purwo as an authentic cultural tourism destination is identified; however, its development requires a sustainable approach that respects the inherent cultural and ecological values. This research recommends tourism development strategies that empower local communities, preserve cultural heritage, and minimize negative impacts on the natural environment of Alas Purwo.